PENGARUH SISTEM INFORMASI AKUNTANSI DAN KETEPATAN PEMBAYARAN PIUTANG TERHADAP PENGENDALIAN INTERNAL PENJUALAN - Rahayu, Peni Firbo (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of accounting information system and payment punctuality of account receivable to the sales internal control at PT Imperium Happy Puppy. The method of research is quantitative method. The sample collection technique is conducted by performing non-probability sampling and saturated sampling technique approach. The primary data is obtained by distributing questionnaires. This research uses several tests which are partial test (t-test) and multiple determination coefficient analysis (R2). The result of the research result shows that the accounting information system (X1) and payment punctuality of account receivable (X2) have significant and positive influence to the sales internal control (Y) at Imperium Happy Puppy head office. Based on the result of questionnaires calculation by using computer program of SSPS (Statistical Package Social Science) V.20.0 for Windows, the multiple determination coefficient analysis (RÂ²) is 0.818 which means that the accounting information system (X1) and payment punctuality of account receivable (X2) has influence 81.8% and the remaining is 18.2% is explained by other variables which are used in this research. The result of research which is based on t test for the accounting information system (X1) and payment punctuality of account receivable (X2) with trust level or significance is 95% and Î± = 0,05. Moreover, the tsign or significance value of each variable is 0.000 and 0.016. Because the significant value of accounting information system and payment punctuality of account receivable is less than Î± (0.000 < 0.05) and (0.016 < 0.05) so the hypothesis is accepted (significant regression coefficient).Keywords: Accounting Information System, the Payment Punctuality of Account Receivable, Sales Internal Control.